A study on the assessment of body image ability with adults - Ahn, Sinae (Edelweiss Applied Science and Technology, 2025)
This study aimed to investigate body image in adults with normal development and to examine the differences between subjective and objective evaluations of body image. The study analyzed the results of evaluating the participants’ body image at a single point in time by dividing it into subjective and objective body perception, according to the research purpose, and applied a cross-sectional study design. Statistical analysis was performed using SPSS for Windows (version 26.0). The statistical significance level was set at 0.05. The findings revealed differences in scores between the subjective body perception of the participants and the objective body perception evaluated by a third party, but there was no statistical difference. This study examined the differences between subjective and objective perspectives on body image in normal adults.